The Role of Sports Training in Developing the Player’s Goal Scoring Skills and Knowing Future Results - Abdyasir, Hussein Ali (Indonesian Journal Publisher, 2023)
This study aimed to know the direct effect of sports training on players according to scoring goal and the predictive value of scoring goals for the age group ranging from 13 to 18 years were divided to two groups, 40 samples and 40 comparison group. It focused on the programming process or practical principles of sports training and the relationship of the physical aspect and its connection to the physical and skill aspects, and the use of the content of traditional training with and without the ball. The coaching profession is considered to be the organization and management of the sports educational experience to become an applied experience for the sports coach. It is a profession that depends first and foremost on individual competence and the ability to impose discipline, which must be present in the coach before working in this profession, so that he must have a high ability to understand training and how to use methods, techniques and technical procedures related to organizing and directing the players’ experiences. The data for this study was collected and analysed using the statistical analysis program SPSS IBM Soft 22.0 where several measures were addressed to determine the type and strength of the statistical relationship between the two groups. After presenting and submitting the results, we concluded the following: there is a weak direct relationship between the first group, which included samples, and increased goal scoring skill, there is a strong direct relationship between basic skills and physical abilities, which is linked to the sports performance of players with the amount of goals scored, there is a strong direct relationship between Assessment outcomes of study according to Expected Goals (xG) With scoring goals in the future.